Efikasnija naplata poreza i sprečavanje poreznih utaja/evazija : prevencija protiv represije - Cipek, Ksenija (Array, 2018)
Here the author analyses the key aspects of Strategies of external and internal communications of the Taxation Department between 2012 to 2015, and the Taxation Department’s vision of strengthening its reputation as a successful institution in the public sector of the Republic of Croatia. Forms of communication which should contribute to the establishment of a flexible approach towards tax payers are elaborated and evaluated. The author concludes that there is a need to focus prevention. Prevention ensures less cost and a better result. Measures of a repressive nature should be efficiently and timely directed towards high risk tax payers. This would achieve optimal use of resources of taxation (external) supervision. Those measures are necessary in order to combat tax evasion.